Role of Information Technology in Indian Banking Sector - sadineni, Praveen Kumar (Universal Research Reports, 2018)
Information technology refers to the acquisition, processing, storage and dissemination of all kinds of data using technology and telecommunication systems. Technology includes all maters concerned with the furtherance of computing and technology and with the planning, development, installation and implementation of data system and applications. Information technology architecture is an integrated framework for acquiring and evolving it to realize strategic goals. Information technology has both logical and technical components. hardware and software, voice, data, network, satellite, other telecommunications technologies, multimedia are application development tools. These technologies are used for the input, storage, processing and communication of data . Information technology includes ancillary equipment, software, firmware and similar procedures, services etc. Modern high throughput technologies are providing vast amounts of the sequences, expressions and functional data for genes and protein. one among the foremost difficult challenges is popping this enormous pool of data into useful scientific insight and novel therapeutic products.